Factors that affect the rehabilitation of stroke patients - Saluta, Enoria S.
This study is an attempt to explore the factors that affect rehabilitation of Filipino stroke patients. It sought to determine whether significant relationships existed between sociodemographic variables (sex, age, civil status, educational attainment, life style and support system) as well as illness variables (diagnosis, initial medical consultation and presence/absence of associated disease conditions) and the patient's rehabilitation score. This dependent variables of rehabilitation score is the patient's composite score on the modified Barthel Index, the tool currently being utilized to monitor the progress of patients at the Stroke Clinic of the Department of Rehabilitation Medicine, Philippine General Hospital. The subject for theses ex-post-facto research study were chosen from among the stroke patients who were treated at the Philippine General Hospital Stroke Clinic for the years 1986-1988. Selection was limited to these patients who were able to complete 3 consecutive months of rehabilitation regimen at the clinic. Documentary analysis of these patients' charts was the main method of data collection. These data were later analyzed by using tests of inferential statistics (Pearson Product Moment Correlation, and Chi-square) as well as descriptive statistics. A relationship between any set of variables was deemed to be statistically significant is the obtained value was greater than or equal to that value representing alpha .05. Findings of this study revealed significant relations between (1) sex and rehabilitation scores (males had higher scores than females); (2) diagnosis and rehabilitation scores (patients with thrombosis scored higher than those who had a diagnosis of hemorrhage of embolism); (3) initial consultation time and rehabilitation scores (an inverse relationship, that is, the earlier the patient consulted a physician health facility after the occurrence of the stroke, the higher the rehabilitation scores); (4) age (that the younger patients received higher rehabilitation scores than the older subjects). Another significant finding is the association between sex and initial consultation (i.e. males tended to seek medical care earlier than females).